What motivated men to start PrEP? A cross-section of men starting PrEP in Buffalo city municipality, South Africa - Philip John Smith; Joseph Daniels; Linda-Gail Bekker; Andrew Medina-Marino (BMC, 2023)
Abstract Background Compared to women, South African men are less likely to know their HIV status (78% vs. 89%), have suppressed viral loads (82% vs. 90%), or access HIV prevention services. To achieve epidemic control where heterosexual sexual behavior drives transmission, interventions to improve the uptake of HIV testing services (HTS) and prevention services must also target cis-gendered, heterosexual men. There is limited understanding of these men's needs and wants with regards to accessing pre-exposure prophylaxis (PrEP). Methods Adult men (≥ 18 years) from a peri-urban community in Buffalo City Municipality were offered community-based HTS. Those who received a negative HIV test result were offered community-based, same-day oral PrEP initiation. Men initiating PrEP were invited to participate in a study exploring men's HIV prevention needs and reasons for initiating PrEP. An in-depth interview guide, developed using the Network-Individual-Resources model (NIRM), explored men's perceived HIV acquisition risk, prevention needs, and preferences for PrEP initiation. Interviews were conducted by a trained interviewer in isiXhosa or English, audio-recorded and transcribed. Thematic analysis was used, guided by the NIRM to generate findings. Results Twenty-two men (age range 18-57 years) initiated PrEP and consented to study participation. Men reported elevated HIV acquisition risk associated with alcohol use and condom-less sex with multiple partners as facilitators driving PrEP initiation. They anticipated social support from family members, their main sexual partner and close friends for their PrEP use, and discussed other men as important sources of support for PrEP initiation. Nearly all men expressed positive views of people using PrEP. Participants believed HIV testing would be a barrier for men interested in accessing PrEP. Men recommended that access to PrEP be convenient, rapid, and community-based (i.e., not clinic-based). Discussion Self-perceived risk for HIV acquisition was a major facilitator for men's PrEP initiation. Although men expressed positive perceptions of PrEP users, they noted that HIV testing may be a barrier to PrEP initiation. Finally, men recommended convenient access points to facilitate PrEP initiation and sustained use. Gender-responsive interventions tailored to men's needs, wants, and voices will facilitate their uptake of HIV prevention services, and help to end the HIV epidemic.